Government debt in times of low interest rates: the case of Europe - Clemens Fuest; Daniel Gros (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
In this paper we discuss to what extent the declining difference between interest rates and growth rates (r-g) pointed out recently by Olivier Blanchard (2019) for the case of the US also characterizes the economic situation in Europe. We show that r-g has been positive on average but declining over the last decades in Europe as well. But r-g differs across considerably across European countries, and a continuation of current fiscal policies even under existing conditions would increase the debt ratios further in some countries. We conclude that the current low levels of r-g should be used to make progress in fiscal consolidation in countries with high debt levels. At the same time it would be desirable to benefit from the currently low interest rates to boost one time investment projects.
Keywords: 330